2019
DOI: 10.1016/j.bone.2019.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Older age at initiation of antiretroviral therapy predicts low bone mineral density in children with perinatally-infected HIV in Zimbabwe

Abstract: Background Perinatally-acquired HIV infection commonly causes stunting in children; how this affects bone and muscle development is unclear. We investigated differences in bone and muscle mass and muscle function between children with HIV (CWH) and uninfected children. Setting Cross-sectional study of CWH (6–16 years) receiving antiretroviral therapy (ART) for >6 months and similar aged children testing HIV-negative at primary health clinics in Zimbabwe. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 34 publications
5
22
0
1
Order By: Relevance
“…This nding is similar to results of a recent study conducted in Thailand, which demonstrated that the younger the children at ART initiation, the greater the effect on height-growth velocity regardless of the ART regimen [35]. Another recent study revealed that HIV infection was associated with not only stunting but also low lumbar spine bone density among children living with HIV in Zimbabwe and that younger age at initiation of ART predicted high bone mineral density [36]. There are additional studies which stress the importance of initiating ART before irreversible stunting has occurred [37].…”
Section: Discussionsupporting
confidence: 88%
“…This nding is similar to results of a recent study conducted in Thailand, which demonstrated that the younger the children at ART initiation, the greater the effect on height-growth velocity regardless of the ART regimen [35]. Another recent study revealed that HIV infection was associated with not only stunting but also low lumbar spine bone density among children living with HIV in Zimbabwe and that younger age at initiation of ART predicted high bone mineral density [36]. There are additional studies which stress the importance of initiating ART before irreversible stunting has occurred [37].…”
Section: Discussionsupporting
confidence: 88%
“…This finding is similar to results of a recent study conducted in Thailand, which demonstrated that the younger the children at ART initiation, the greater the effect on height-growth velocity regardless of the ART regimen [Traisathit]. Another recent study revealed that HIV infection was associated with not only stunting but also low lumbar spine bone density among children living with HIV in Zimbabwe and that younger age at initiation of ART predicted high bone mineral density [30]. There are additional studies which stress the importance of initiating ART before irreversible stunting has occurred [31].…”
Section: Discussionsupporting
confidence: 88%
“…A recent study from Zimbabwe showed reduced size-adjusted (Z-Score ≤ -2.0) lumbar spine total-body-less head bone density measurements in 15% and 13% of CWHIV aged 8 to 16 years taking ART. 48 Notably, this study used 'gold-standard' size adjustment methods for analysing dual X-ray absorptiometry scans which, if ignored, underestimate bone density in stunted children. 49 Certain ART drugs such as TDF may cause accelerated bone loss, likely aggravated by both low body mass and vitamin D deficiency.…”
Section: Renal and Metabolic Diseasementioning
confidence: 99%
“…34 While studies have reported an association of TDF with lower bone density in CWHIV, this association may not be sustained longterm and longitudinal studies from SSA are needed to determine the impact of TDF on bone health in children. 34,48,50 Additional factors, prevalent among CWHIV, can further compromise bone health, including low muscle mass, poor nutrition, inadequate dietary calcium, vitamin D deficiency and the HIV-associated pro-inflammatory milieu. [51][52][53] Muscle strength and bone strength are closely related; muscles exert forces on bone resulting in bone adaptation in size and strength.…”
Section: Renal and Metabolic Diseasementioning
confidence: 99%
See 1 more Smart Citation